2021
DOI: 10.1002/jor.25020
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing anterior cruciate ligament reconstruction: Individualizing the decision‐making process using data from the Kaiser Permanente ACLR Registry: 2018 OREF award paper

Abstract: Despite years of study, controversy remains regarding the optimal graft for anterior cruciate ligament reconstruction (ACLR), suggesting that a single graft type is not ideal for all patients. A large community based ACLR Registry that collects prospective data is a powerful tool that captures information and can be analyzed to optimize surgery for individual patients. The studies highlighted in this paper were designed to optimize and individualize ACLR surgery and have led to changes in surgeon behavior and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“… 13 , 15 , 21 , 23 Allografts avoid the effect of reducing dynamic control of the medial knee, 13 but in ACL reconstruction, at least, they have higher failure rates. 28 Furthermore, there is no reason to suspect that the findings of this biomechanical study should not be applicable with autogenic or allogenic tendon grafts.…”
Section: Discussionmentioning
confidence: 92%
“… 13 , 15 , 21 , 23 Allografts avoid the effect of reducing dynamic control of the medial knee, 13 but in ACL reconstruction, at least, they have higher failure rates. 28 Furthermore, there is no reason to suspect that the findings of this biomechanical study should not be applicable with autogenic or allogenic tendon grafts.…”
Section: Discussionmentioning
confidence: 92%
“…Previous registry-based studies confirm the use of HT as the most common autograft choice [ 25 , 32 , 33 ]. Additionally, studies investigating surgeon preference found a predilection for HT autografts in primary ACLR [ 14 , 52 ].…”
Section: Discussionmentioning
confidence: 97%
“…The graft choice based on patient sex is in agreement with previous reports from national ACL registries and surgeon surveys [ 21 , 33 , 52 ], but the underlying reasons are still somewhat unclear. While female sex has been identified as a risk factor for primary ACL injury, there is conflicting evidence regarding the risk of graft rupture and revision rates between the sexes [ 3 , 5 , 25 , 43 , 45 ]. In terms of graft characteristics, a few studies have found an increase in objective knee stability and a lower incidence of graft rupture in primary ACLRs with PT compared with HT autografts among young females [ 35 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“… 24 , 39 This evidence led to a decrease in allograft use in patients aged ≤21 years from a peak of 28% in 2009 down to 9% in 2015 in one large registry. 20 In 2014, the American Academy of Orthopedic Surgeons published a clinical practice guideline that stated surgeons could use “autograft or appropriately processed allograft…because the measured outcomes are similar, although these results may not be generalizable to all allografts or all patients, such as young patients or highly active patients.” 1 This literature suggests that around 2015 is when more narrowed indications for allograft use became widespread. This aligns with the beginning of the time interval for patient collection used in the present study to ensure that most allograft use was applied with a modern understanding of indications for allograft use in ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%